Producción del cultivo de maracuyá (Passiflora edulis) en el Ecuador - Estrada Guanoluisa, Yulissa Paola (2024)
Passion fruit in Ecuador represents a non-traditional fruit crop as a sustainable and profitable alternative for Ecuadorian agricultural producers, because this fruit has a high demand in the international market, generating employment and foreign exchange that contributes to boosting the rural economy in the productive areas. The information obtained was carried out through the analysis, synthesis and summary technique. Due to the above details, within the production of passion fruit cultivation there are various edaphoclimatic factors that intervene in the yield and quality of the crop, the following being the most relevant: temperature, relative humidity, altitude, wind, heliophany, precipitation and soils. Passion fruit cultivation requires an optimal temperature range of 23-25°C; although its adaptation temperature is between 21 and 32°C; the same one that is related to an altitude of 300 to 900 meters. Passion fruit requires a relative humidity of 80% to promote pollen viability and receptivity to important pollination factors and for high, uniform fertilization. The passion fruit is a tropical climate plant that requires a water supply with an annual deposit of 800 to 1750 mm distributed evenly throughout the 12 months of the year. Passion fruit is a photoperiodic plant that needs at least 11 hours of light a day to flower; If the daylight hours are short and the light duration is less than this number of hours, flower production decreases. In the production of passion fruit crops there are agronomic factors that intervene such as: propagation, sowing, sowing density, soil preparation, furrowing, pitting, staking, pruning, irrigation, weed control, fertilization, pest management and harvest.